Laparoscopic Kasai portoenterostomy for biliary atresia: first experience from Central Asia - Semash, Konstantin; Nasirov, Mansur; Dzhanbekov, Timur; Khudaybergenova, Ayimgul (Frontiers in Pediatrics, 2025)
ObjectiveBiliary atresia (BA) is a progressive fibro-obliterative disease of the extrahepatic bile ducts. Laparoscopic Kasai portoenterostomy (LKPE) has emerged as a minimally invasive alternative to the open approach. We aimed to evaluate the feasibility, perioperative outcomes, and early prognostic factors of LKPE in a single center.MethodsWe conducted a retrospective single-center study. Feasibility, operative metrics (including the learning curve), incidence of cholangitis, native liver survival, and clinical outcomes were assessed using standard statistical methods.ResultsAmong the 33 patients (14 females, 19 males), the age at surgery was <60 days (12 patients), 60–89 days (13 patients), and >90 days (8 patients). The median operative time was 240 min, showing a declining trend with increasing experience. One conversion (1/33) to open surgery was required due to inadequate hilar visualization. Postoperative cholangitis occurred in 51.5% of cases and was associated with an increased risk of native liver failure (HR = 3.6, p = 0.051). The native liver survival rate at study completion was 54.5%, with 5 patients (15.2%) requiring liver transplantation. The overall mortality rate was 30.3%, primarily due to sepsis and cholangitis-related complications.ConclusionsLKPE is a feasible and effective surgical option for biliary atresia. Despite its advantages, including enhanced hilar visualization and faster recovery, the high incidence of postoperative cholangitis remains a major challenge that adversely affects native liver survival. Optimizing perioperative management, implementing prophylactic strategies against cholangitis, and expanding pediatric liver transplantation programs in resource-limited settings are essential to improving outcomes. Further prospective studies with long-term follow-up are needed to refine surgical techniques and optimize patient management.